A class of linear codes with good parameters from algebraic curves - Xing, Chaoping (2012)
A class of linear codes with good parameters is constructed in this correspondence. It turns out that linear codes of this class are subcodes of the subfield subcodes of Goppa's geometry codes. In particular, we find 61 improvements on Brouwer's table based on our codes.